2016
DOI: 10.3892/ol.2016.5425
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of the expression of Nm23-H1 and p53 is correlated with survival rates of patients with stage II and III colorectal cancer

Abstract: Molecular tumor markers hold considerable promise for accurately predicting the recurrence and progression of colorectal cancer (CRC) in patients. However, in the majority of cases, single marker analysis has been found to have low accuracy, and is of little practical use in clinical practice. The present study investigated the prognostic value of the combined detection of the protein expression of metastasis suppressor 23-H1 (Nm23-H1) and p53 using immunohistochemical analysis, and the mRNA expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
5
0
5
Order By: Relevance
“…NME1 plays a significant role in regulation of p53 function 23 , 24 . NME1 stabilizes p53 by interacting with p53 and suppressing the interaction of p53 with MDM2 25 .…”
Section: Resultsmentioning
confidence: 99%
“…NME1 plays a significant role in regulation of p53 function 23 , 24 . NME1 stabilizes p53 by interacting with p53 and suppressing the interaction of p53 with MDM2 25 .…”
Section: Resultsmentioning
confidence: 99%
“…O CCR é um tumor com elevadas taxas de incidência e mortalidade, [8][9] tanto no ocidente quanto no oriente, crescendo em incidência a 4,2% por ano na China. 9 O adenoma colorretal é considerado um precursor de seu desenvolvimento, 8,10 que junto a processos genéticos complexos, leva a sua origem.…”
Section: Resultsunclassified
“…O TP53, presente no cromossomo 17p, codifica a proteína p53, que é responsável pela regulação do ciclo celular. [5][6][7][8][9][10][11] A mutação do TP53, o evento mais comum nos carcinomas humanos, 4,5,11 leva ao acúmulo de p53 mutante, que tem meia vida maior que a p53 selvagem 10,[12][13] , possibilitando sua coloração e visualização no núcleo celular através da IHQ. [6][7][8][9][10][11] Sob a IHQ, o núcleo da célula apresenta grânulos marrons quando positiva para p53.…”
Section: Resultsunclassified
“…The function of nm23 in human cancer is currently unconfirmed (22,(28)(29)(30)(31), and certain reports have indicated there is a link between high expression of the nm-23 gene and its protein product with low metastatic potential of cancer (28). Nm-23 is known to be associated with early onset of familial breast and ovarian cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism by which nm-23 regulates metastasis is not fully understood, experimental data have shown that nm23 serves an important role in the regulation of metastasis in a number of human cancer types (29). It was also reported that nm-23 expression was a significant factor for predicting a favorable prognosis, suggesting the anti-metastatic potential of nm-23 in NSCLC (30,31). The expression of nm23 in normal lung tissue was much higher than in cancer tissues, and was associated with staging and lymphatic metastasis, and this may suggest that the absence of nm23 expression may serve an important role in the incidence of NSCLC.…”
Section: Discussionmentioning
confidence: 99%